The tourism and agrotourism potential of the Tulcea and Vrancea Counties: Comparison - Eugenia-Dorina Ciobanu; Petruța Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Being part of the South-East Region of the country, Tulcea County as well as Vrancea County are important tourism areas, with high tourist potential, harmoniously distributed throughout the counties territories. Tulcea County is a gate towards the Danube Delta Biosphere Reservation, ranked on the third place by ecological importance in the world, is a tourism destination unique in our country, with large possibilities of development. Throughout the County there are 1 Municipality, 5 cities, 46 de parishes and 133 villages, which means that the area is mostly rural. Vrancea County, located at Muntenia's borderline to Moldova, in the area of the Curvature Carpathians, is also an important tourist area with real chances of increasing the capitalizing degree of existing tourism potential. It consists of 1 Municipality, 4 cities, 64 parishes and 331 villages, the rural area being dominant here also. The standard of living of the inhabitants from the rural area, in both counties is not a very good one, poverty being the problem which the inhabitants have been facing for years, in spite of the tourism potential that is not capitalized to its maximum. The present article aims to analyze the tourist potential of the counties, to show the problems that limit the tourism activity and to highlight a few development and capitalizing possibilities of the tourist potential, on full capacity.
Keywords: Q11; 330; tourism; agrotourism; tourist potential; tourist activity